Contents & Introduction, Law Text Culture, volume 24 - James Parker; Sara Ramshaw; Mehera San Roque (Law Text Culture, 2020)
This essay introduces a large and diverse special issue on ‘The Acoustics of Justice: Law, Listening, Sound’. Until recently the acoustic dimensions of law and justice were not a major concern in the academy, either in self-consciously legal scholarship, or elsewhere. Things are changing, as indeed the size of this collection suggests. And our hope is that the work gathered here will go some way to addressing this deficit. Nevertheless, this introduction does not attempt to theorise how. Though the collection was conceived in 2019, it was mostly produced since the arrival of COVID-19. And we are tired. We have been working from home too long; or rather our homes have been ‘requisitioned’ for work. Our teaching loads have increased and the teaching itself rapidly onlined. All while separated from loved ones and attempting to school or otherwise entertain our kids at home. And we are the lucky ones. This introduction is, in a sense, an anti-introduction, or a non-introduction then: a strategic withdrawal of labour that opens the door onto the collection but offers little in the way of guidance to readers once they step through. Whether that is generous or irresponsible we leave to readers to decide.